2021
DOI: 10.29023/alanyaakademik.871031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Financial Performance of Foreign Banks Having Branches in Turkey by TOPSIS and ELECTRE Methods

Abstract: Effective performance evaluation is an important indicator of the success of every business particularly the banking sector. Banks are one of the most fundamental elements of the financial system. The financial structures of banks should be measured and evaluated accurately, the results should be analyzed salubriously and presented to the relevant users. The performance of each bank is evaluated by financial criteria which are ranked according to their financial performance. This is important both for the bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…When the results obtained with the CRITIC-based PROMETHEE and EDAS model applied considering all years; among the 21 banks with the highest financial performance, Ziraat Bank of the Republic of Türkiye (BKK1), one of the stateowned banks, ranked first. This result is included in the literature it was similar to the studies conducted by Akbulut (2020), Aydın (2020a), Bayram (2020), Çelik (2020), Eş and Kök (2020), Sarı (2020), Ünvan (2020), Bayram (2021), Bozdoğan, Odabaş and Shegiwal (2021), Yetiz and Kılıç (2021), Karahan and Kızkapan (2022), Say (2022) and Yılmaz (2022). On the other hand, for future studies, it may be suggested to apply different sorting and weighting methods, to include non-financial ratios such as customer satisfaction and number of bank branches in addition to financial ratios, and to expand the size of the study by using different samples.…”
Section: çAtışma Beyanısupporting
confidence: 83%
See 1 more Smart Citation
“…When the results obtained with the CRITIC-based PROMETHEE and EDAS model applied considering all years; among the 21 banks with the highest financial performance, Ziraat Bank of the Republic of Türkiye (BKK1), one of the stateowned banks, ranked first. This result is included in the literature it was similar to the studies conducted by Akbulut (2020), Aydın (2020a), Bayram (2020), Çelik (2020), Eş and Kök (2020), Sarı (2020), Ünvan (2020), Bayram (2021), Bozdoğan, Odabaş and Shegiwal (2021), Yetiz and Kılıç (2021), Karahan and Kızkapan (2022), Say (2022) and Yılmaz (2022). On the other hand, for future studies, it may be suggested to apply different sorting and weighting methods, to include non-financial ratios such as customer satisfaction and number of bank branches in addition to financial ratios, and to expand the size of the study by using different samples.…”
Section: çAtışma Beyanısupporting
confidence: 83%
“…Çalışmada bankaların finansal performanslarını belirlemek amacıyla PROMETHEE ve EDAS yöntemi analiz sonuçlarına göre, bankaların finansal performans düzeyleri incelendiğinde; en yüksek ilk üç bankanın sırasıyla kamu sermayeli bankalardan Ziraat Bankası'nın, özel sermayeli bankalardan İş Bankası'nın, yabancı sermayeli bankalardan ise Garanti Bankası'nın olduğu saptanmıştır. Benzer şekilde literatürde yapılan çalışmalara göre bankaların finansal performans sıralamaları incelendiğinde Ziraat Bankası'nın ilk sırada olduğu çalışmalar mevcuttur (Akbulut, 2020;Aydın, 2020a;Bayram, 2020;Çelik, 2020;Eş ve Kök, 2020;Sarı, 2020;Ünvan, 2020;Bayram, 2021;Bozdoğan, Odabaş ve Shegiwal, 2021;Yetiz ve Kılıç, 2021;Karahan ve Kızkapan, 2022;Say, 2022;Yılmaz, 2022). Buna karşın farklı sıralama sonucu elde edilen çalışmaların da olduğu dikkat çekmiştir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…On the other hand, MCDM enables a partial function analysis of banking performance in terms of specific financial variables provided by the expert preferences (or weights) that are defined exogenously to the positive ideal performance [25]. For instance Bozdogan et al [26] evaluated performance of Turkish bank with TOPSIS and ELEC-TRE. Marjanovic and Popivic [27] evaluated Serbian bank with CRITIC and TOPSIS methods.…”
Section: Literature Review a Unveiling The Relationships Among Camels...mentioning
confidence: 99%
“…Banks that make profits through investments are among the financial institutions that redistribute unused resources and competencies from areas of excess funds to areas of need [1], [2]. Every day, banks handle millions of transactions, such as providing credit cards, lending money for short-or long-term loans, opening LCs, and performing other activities that help to maintain liquidity in the market.…”
Section: Introductionmentioning
confidence: 99%